Fluorescence properties of fluorenylidene bridged cyclotriphosphazenes bearing aryloxy groups. (14th December 2015) - Çiftçi, Gönül Yenilmez; Şenkuytu, Elif; İncir, Elif Saadet; Durmuş, Mahmut; Yuksel, Fatma
Graphical abstract: The synthesis and characterization of the first series of open chain and aryloxy full-substituted fluorenylidene open chain and bridged cyclotriphosphazene derivatives (13 –18 ) is reported in this study. The structural investigations of the compounds were verified by elemental analyses, mass spectrometry, UV–Vis, FT-IR, 1 H and 31 P NMR techniques, and X-ray crystallography (for13 and18 ). The fluorescence behavior of the studied cyclotriphosphazene derivatives was also examined in THF solution. Compound16 showed a high enough emission among the studied compounds to study its metal sensing properties. This compound showed high selectivity for copper (Cu 2+ ) and iron (Fe 2+ /Fe 3+ ) ions in solution. Abstract: The synthesis and characterization of the first series of aryloxy full-substituted fluorenylidene open chain and bridged cyclotriphosphazene derivatives (13 –18 ) are reported in this study. The synthetic route utilized includes the reaction of penta-substituted cyclotriphosphazenes (5, 7, 9 ) with 4, 4′-(9-fluorenylidene)diphenol (FDP ) (11 ) and 4, 4′-(9-fluorenylidene)dianiline (FDA ) (12 ) to give bridged compounds (13, 15 –17 ) and open chain compounds (14 and18 ). The structural investigations of the compounds were verified by elemental analyses, mass spectrometry, UV–Vis, FT-IR, 1 H and 31 P NMR techniques, and X-ray crystallography (for13 and18 ). The fluorescence behavior of the studied cyclotriphosphazene derivatives were also examined in THF solution. Compound16 showed a high emission among the studied compounds to investigate its metal sensing properties. This compound showed high selectivity for copper (Cu 2+ ) and iron (Fe 2+ /Fe 3+ ) ions in solution.